Reactivity of 4-hydroxy-2-pyrones in the diels-alder reactions - Tanyeli, Cihangir; Tarhan, Okan Okan (My University, 1989)
Biphenylcarboxylic acid derivatives, and some tptracyclic bridge cycloadducts have been prepared by Diels-Alder reactions of acetylenic and prepared dienophiles with 4-hydroxy-6-phenyl-2H-pyran-2-one and its methyl ether derivative. © 1989, Taylor & Francis Group, LLC. All rights reserved.